Determining the Effectiveness of Promotion and Reviews of Bollywood Films from Audiences : An Empirical Study - Thomas, Frince C.; Patel, Naresh K. (Indian Journal of Marketing, 2020)
Purpose: The study aimed to upsurge box-office revenue of films. Objective: The broad aim of the proposed study was to find out the effectiveness of various promotion and reviews of Bollywood films from audiences. Design/Methodology/Approach: Data were collected from 1165 respondents of dissimilar age groups and genders. The questionnaire was created by using a Likert scale and managed by using convenience sampling. Originality/Value: The paper adds theoretical, empirical depth, and probe to the study approach and preferences of audiences towards promotion and reviews of Bollywood films. The role of reviews and promotions in the film-making process and its effectiveness from audiences are not keenly researched in India. The study, therefore, aimed to unearth the effective mediums for promotion of films and to study the audiences' preferences towards reviews before, during, and after the release of films. Future Research Scope: Future research can benefit from further advances in measuring techniques and also by using a greater volley of questions. Even in the case of awareness campaigns, they might well vary in other countries or at times. Future research should address the generalizability of our findings across time periods and geographical settings. It is proposed that further research needs to be done for the validation of the findings of the present study. Practical Implications: The findings can provide some significant scope for directors, film reviewers, and marketers in direction, reviews, and promotions, respectively.